Measurement results of flow downstream from the cylinder - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The flow downstream from a cylinder positioned normal to the flow in an open channel has been investigated experimentally. An Acoustic Doppler Velocity Profiler (AD VP) was used to obtain instantaneously. the three directions of the mean velocity. Two types of flow were studied. Results of the experiments show that a vertical vortex is established